2019
DOI: 10.2196/11989
|View full text |Cite
|
Sign up to set email alerts
|

Wearable-Based Mobile Health App in Gastric Cancer Patients for Postoperative Physical Activity Monitoring: Focus Group Study

Abstract: Background Surgical cancer patients often have deteriorated physical activity (PA), which in turn, contributes to poor outcomes and early recurrence of cancer. Mobile health (mHealth) platforms are progressively used for monitoring clinical conditions in medical subjects. Despite prevalent enthusiasm for the use of mHealth, limited studies have applied these platforms to surgical patients who are in much need of care because of acutely significant loss of physical function during the postoperative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 55 publications
(52 reference statements)
2
37
0
1
Order By: Relevance
“…Generally, medical practitioners are often swamped with clinical responsibilities that they do not have enough time to conduct a routine assessment, discussion, and plan of physical fitness for patients. Fortunately, with information and communication technologies progressing and developing, facilities with internet of things technology such as wearable devices and smartphones have carried out appropriate approaches, along with objective quantitative data, for measurement and management in physical fitness and physical activity [ 59 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, medical practitioners are often swamped with clinical responsibilities that they do not have enough time to conduct a routine assessment, discussion, and plan of physical fitness for patients. Fortunately, with information and communication technologies progressing and developing, facilities with internet of things technology such as wearable devices and smartphones have carried out appropriate approaches, along with objective quantitative data, for measurement and management in physical fitness and physical activity [ 59 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, mHealth is a scalable and flexible platform supporting the practice of medical and perioperative care with the provision of mobile devices [8,[21][22][23], which improve the quality of perioperative care and have proliferated [24,25]. Although some academic centers have developed the mHealth system for postoperative wound care with positive results, it places an additional strain and workload on their provider teams, even if they are enthusiastic about it [5,7,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the surgical staff would make a call to inquire the patients of the recovery of the general condition and the wound, whereas the condition of the wound is difficult to be remotely evaluated by verbal communications only. To reduce the gap between home and hospital, mobile health (mHealth) has been created to help patients upload wound images and obtain immediate responses regarding their wound condition and has proved feasible in several studies [6][7][8]. Furthermore, the patients receive feelings of reassurance because the medical staff continuously and seamlessly monitor their recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Among studies focusing on the application of mHealth to surgical issues, several have investigated wound care and pain scaling to validate the clinical usefulness of mHealth [ 54 - 57 ]. A recent study used another wearable device to track the step counts of patients who had undergone various abdominal surgeries for 1 month after discharge and showed that the mHealth app could effectively track recovery [ 24 , 58 ]. Because drain care is an issue that is unique to surgical patients, and telephone conversations and questionnaires cannot be used to access the visual component.…”
Section: Discussionmentioning
confidence: 99%
“…As the ownership of mobile devices has become more common [ 17 ], patients and their caregivers are increasingly willing to use technology to access health care [ 18 , 19 ]. Several studies have demonstrated that mHealth technology improves the control of cardiac function and glycemic hemostasis, enhances medication compliance, and shortens hospital stays [ 20 - 24 ]. Additionally, prior research on app protocols for surgical patients has focused on routine procedures that already have a low baseline rate of postoperative and discharge complications [ 25 - 27 ].…”
Section: Introductionmentioning
confidence: 99%